Continuous assessment of cowpea [Vigna unguiculata L. Walp.] nutritional status using diagnosis and recommendation integrated system approach - AGBANGBA, Codjo Emile; DAGBENONBAKIN, Gustave D.; AMADJI, LUCIEN GUILLAUME (My University, 2023)
Cowpea is one of the widely cultivated and consumed grain legumes in Africa, but its production is hampered by soil fertility degradation on farms. Here, we assessed the spatial nutritional diagnosis of cowpea and the variability of their productivity using the diagnosis and recommendation integrated system (DRIS) and geostatistics tool. We achieved a sampling of 200 geo-referred points in cowpea farms in four communes of Benin. In addition, we determined grain yield and the content of N, P, K, Ca, Mg, and Zn in the leaves. From DRIS, the order of nutrient defciency was as follows: P>K>Ca >Zn>N>Mg; P>K>Ca >N>Zn>Mg; N>Mg>Zn>K>P>Ca; P>Ca >K>N>Mg>Zn, at DassaZoume, Glazoue, Ketou, and Ouesse, respectively. Sampling points were close enough to detect the spatial variability of the DRIS Index, mean of nutrient balance index (NBIm), and cowpea productivity (spatial dependence index ˃ 50%). The combined analysis of the cowpea relative yield and NBIm maps showed that the NBIm map effectively indicated the spatial distribution of cowpea productivity. The spatial variability of the DRIS index has provided an accurate guide to where adjustments to fertilization rates are needed.
Keywords: DRIS; Model; Spatial Variability; Nutrient Diagnosis